Using steam to dry food: introducing the (UPoCA) dryer - Nonie, S.E.B.; James, B.D.; Alpha, S.J. (International Association of Hydrological Sciences, 2012)
The production of cassava flour involves drying grated and pressed cassava into pellets that are milled into flour. The drying process is one of the major bottlenecks to expanding the economic value of the crop. The industry looks for fast drying systems with high flour production capacity to meet market demands. Traditional sun-drying is limited by rainfall, and conventional drying systems are based on motorized machinery unsuitable for farm gate use. The UPoCA dryer has been developed to address these constraints in the production of cassava flours by small to medium processing units. In its standard form, drying system comprises a boiler (325 litres) and two drying cabinets constructed of timber/plywood lined with aluminium sheets. The boiler generates steam that circulates through 7 to 11 shelves of copper coils on top of each is placed a sample tray measuring 1.2m x 0.75m. The coil heats the sample tray and steam from mashed cassava in the tray is removed by convection current of ambient air taken into through the vent holes and dampers. In trials, each cabinet produced 14 to 20 kg dried cassava flour in two hours. With two cabinets operating, the production capacity over an eight to ten-hour working day is about 168 kg and 240 kg for the short, and tall version, respectively. Each version required only three (3) people for regular daily operation. The boiler can operate up to four (4) drying chambers to double the production capacity. The major advantage of this system is that its operation does not require moving parts such as blowers and fans that would require regular maintenance. The system is particularly suited to small scale farming communities in the rural setting, utilising firewood, or charcoal as the fuel source. The application of this device to vegetables and other crops has been tested, with promising results.